2016
DOI: 10.1021/jacs.6b01615
|View full text |Cite
|
Sign up to set email alerts
|

Ru-Catalyzed C–H Arylation of Fluoroarenes with Aryl Halides

Abstract: Although the ruthenium-catalyzed C–H arylation of arenes bearing directing groups with haloarenes is well-known, this process has never been achieved in the absence of directing groups. We report the first example of such a process and show that unexpectedly the reaction only takes place in the presence of catalytic amounts of a benzoic acid. Furthermore, contrary to other transition metals, the arylation site selectivity is governed by both electronic and steric factors. Stoichiometric and NMR mechanistic stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
69
0
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 130 publications
(71 citation statements)
references
References 116 publications
1
69
0
1
Order By: Relevance
“…Examination of other alkali carbonate bases, as well as phosphines, pyridines and NHC‐type ligands did not result in any improvement in the yield of 3 aa . The addition of KOPiv (entry 4) further increased the formation of 3 aa to 51 %, possibly by assisting the C−H activation via a concerted metalation‐deprotonation (CMD) type pathway ,. Interestingly, when potassium perfluoro tert ‐butoxide was used instead of KOPiv, 3 aa was formed in 61 % yield (entry 5).…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations
“…Examination of other alkali carbonate bases, as well as phosphines, pyridines and NHC‐type ligands did not result in any improvement in the yield of 3 aa . The addition of KOPiv (entry 4) further increased the formation of 3 aa to 51 %, possibly by assisting the C−H activation via a concerted metalation‐deprotonation (CMD) type pathway ,. Interestingly, when potassium perfluoro tert ‐butoxide was used instead of KOPiv, 3 aa was formed in 61 % yield (entry 5).…”
Section: Methodsmentioning
confidence: 99%
“…Interestingly, when potassium perfluoro tert ‐butoxide was used instead of KOPiv, 3 aa was formed in 61 % yield (entry 5). We recently disclosed the higher activity of polyfluorinated alkoxide salts over more classical bases commonly employed to facilitate the metalation step . The ability of polyfluoroalcohols in promoting hydrogen‐bonding in the presence of a suitable proton acceptor, while maintaining a low concentration of acidic protons in solution in view of their relative low boiling points, might provide a reasonable explanation behind their exceptional reactivity.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[10][11][12] We started our investigations with 4-tert-butyl-phenol (2a) as model substrate. [14] None of the other Ru precursors that we tried yielded abetter result. Instead of aC ÀNb ond coupledp roduct, however,w ewere surprisedt of ind the dehydrogenative CÀOb ond-formingp roduct, in whicht he phenol is not at all the CÀHs ubstrate, but rathert he exclusive OÀHs ubstrate.I ntrigued, we optimized the reactionf urther,b ya pplying and adjusting typical Ru-catalyzed CÀHa ctivation conditions.…”
mentioning
confidence: 89%
“…[30] In this work, the authors demonstrated how a fundamentalm echanistic understanding could play ac rucial role in the developmento fm ore efficient transformations. A thoroughm echanistic investigation of the previously proposed Ru II/IV catalytic cycle [31] allowed them to uncover key unprecedented mechanisticf eatures:1 ) p-cymene type-ligands (e.g., 1 Ru -MeCN;S cheme 23), widely used in theseR u-catalyzed transformations, [32] inhibited the directed arylation reaction; 2) the employment of a p-cymene-free ruthenacycle, 2 Ru -MeCN,a fforded fasterp roduct formation; [30,33] and3 )the formation of ab is-cycloruthenated Ru II intermediate, 3 Ru -MeCN, prior to the oxidative addition step, was confirmed, which revealed that as econd CÀHa ctivation step occurredb efore accessingt he high-valent Ru IV species( Scheme 23). Based on their experimental results, the authors proposedanew mechanistic hypothesis, which involved ab is-cycloruthenated intermediate, as an alternative to the widely accepted catalytic cycle (Scheme 24).…”
Section: Ruthenium-catalyzed Càhl Ate-stage Functionalizationmentioning
confidence: 99%